Hubungan Penerapan Fungsi Manajemen Keperawatan dengan Model Asuhan Keperawatan Profesional (MAKP) Metode Tim di Ruang Perawatan Nilam Badan Layanan Umum Daerah Rumah Sakit Benyamin Guluh Kabupaten Kolaka Tahun 2014 - Sulaeman, Sulaeman; Riski, Sartini (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2016)
The patchouli treatment room was formed in 2012, the application of nursing management functions such as planning, organizing, directing and controlling has not been optimal which has an impact on the implementation of MAKP. The TIM method in the room is also not optimal. This is because understanding is still limited, there is no training for nurses on the TIM MAKP method and nursing management which has an impact on the quality of nursing services. This type of research is an analytic study with a cross sectional approach. The population in this study were all nurses in the patchouli care room BLUD Benyamin Guluh Hospital with a sampling technique of 24 nurses total sampling. The results of this study indicate that there is a relationship between planning and the application of the team method (p = 0.036 < = 0.05), there is a relationship between organizing and the application of the team method (p = 0.033 < = 0.05), there is a relationship between direction and implementation. the team method (p=0.013 < =0.05), there is a relationship between control and the application of the team method (p=0.002 < =0.05). It is hoped that the treatment room at the BLUD of Benyamin Guluh Hospital can apply a professional nursing care model using the team method through a nursing management function approach